Великие философы: словарь-справочник / Л. В. Блинников - Блинников Леонтий Васильевич (Логос, 1998)
Экземпляры: ЦБ (1998 г.) / Инвентарный номер: 32160 / Цена: 22.00 / Авт.знак: Б 69 / ГРНТИ: 02 / ББК: 87.3я2